Dividend payout ratios as determinants of earnings response coefficients - Kallapur, Sanjay (Journal of Accounting and Economics, 1994)
This paper tests Jensen's (1986a) free cash flow theory that managers overinvest retained earnings by undertaking negative-NPV projects. The test is based on the theory's implication that earnings response coefficients depend positively on payout ratios. It is supported by the data for a sample of 112 firms over the 1951–1986 period. Another test finds that the returns on retained earnings are lower than proxies for the market's required rate of return, as implied by the free cash flow theory. However, the sample firms' Jensen alphas are reliably positive, suggesting that caution is warranted in interpreting the results.